FORECASTING INTERNATIONAL TOURISM DEMAND FOR ECUADOR - Paladines Amaiquema, Jesser Roberto; Amaiquema Illesca, Lourdes (International Journal of Research -GRANTHAALAYAH, 2017)
The international tourism demand for Ecuador was forecasted in this paper, with monthly data of foreign arrivals to Ecuador for the period 2000 to 2016. The Box-Jenkins model was applied, specifically the technique called ARIMA, in order to stablish the best fit to the foreign arrivals from the monthly period from January to June of 2017. According to results, the model was no statistically significant, residual correlations problem was found.